1984
DOI: 10.1139/m84-069
|View full text |Cite
|
Sign up to set email alerts
|

An assay for the measurement of the protein content of cells immobilized in carrageenan

Abstract: A reliable and reproducible method for the estimation of the protein content of fungal cells immobilized in a carrageenan gel is described. The procedure depends upon the acid lability of the polysaccharide gel at 90 degrees C and on the acetone solubility of accumulated phenolics. Freeze-dried gel beads (2-3 mm) containing entrapped cells of Penicillium urticae were ground to a fine powder and samples of powder (approximately 20 mg) were sequentially extracted with hot 1 N HCl - 0.9% NaCl and acetone. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…In Part 1 of this study (Berk et al, 1983), we have shown that the batch production of patulin by immobilized Penicillium urricae cells in the initial stages follows a Type 111 fermentation. Moreover by developing a medium which retarded growth, it was possible to produce patulin in a three phase fluidized bed by immobilized P .…”
Section: I20mentioning
confidence: 85%
See 2 more Smart Citations
“…In Part 1 of this study (Berk et al, 1983), we have shown that the batch production of patulin by immobilized Penicillium urricae cells in the initial stages follows a Type 111 fermentation. Moreover by developing a medium which retarded growth, it was possible to produce patulin in a three phase fluidized bed by immobilized P .…”
Section: I20mentioning
confidence: 85%
“…The growth of the organism, the operation of the continuous reactors and the analytical methods are described in Part 1 of this study (Berk et al, 1983). The composition of the medium that was used in all runs is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effluent samples were directly analyzed for glucose content by the Worthington glucostat enzymatic assay procedure. The protein content of the beads was determined by an assay developed by Jones et al, 1983. In this assay, the freeze-dried beads containing the immobilized cells are ground to a fine powder, and samples of this powder (-20 mg) are extracted first with hot (90°C) 1 N HCI + 0.9% NaCl solution then with acetone.…”
Section: Methodsmentioning
confidence: 99%
“…The protein content of the crude filtered homogenate was assayed by the method of Lowry et al (195 1) after sample preparation as described by Jones et al (1984).…”
Section: Protein Assaymentioning
confidence: 99%